Feeding style profiles are associated with maternal and infant characteristics and infant feeding practices and weight outcomes in African American mothers and infants. (1st May 2021) - Thompson, Amanda L.; Wasser, Heather; Nulty, Alison; Bentley, Margaret E.
Abstract: Much literature links individual feeding styles to infant feeding practices and growth; however, parents' feeding styles are not discrete and may vary by context. We use latent profile analysis (LPA) as a person-centered approach to categorize infant feeding style patterns, test factors predicting profile membership, and examine if profiles are associated with infant feeding and weight. Additionally, we test the impact of a responsive feeding intervention on profile membership and stability. Data come from 270 African-American women and infants participating in the Mothers and Others Study, an early life obesity prevention intervention. LPA was used to categorize mothers across five constructs (laissez-faire, pressuring, restrictive, responsive and indulgent) measured at 28-weeks gestation and 3- and 15-months postpartum. Adjusted multinomial regression and regression models test the characteristics associated with profile membership and the associations between profile membership and breastfeeding and infant weight-for-age z-score (WAZ). We identified two groups (Positive and Less Responsive) prenatally, an additional group (High Controlling) at 3 months and a fourth group (High Indulgent) at 15 months. Several characteristics differed between the groups, including maternal age, income and depressive symptoms, infant sex and temperament, and treatment group. Mothers in the Positive group were more likely to breastfeed at 3 months. Infants with mothers in the High Controlling group had higher WAZ at 15 months. The intervention was associated with more Positive feeding practices at 15 months and a greater likelihood of remaining in the Positive group across the study. LPA identified profiles that are associated with maternal and infant characteristics and treatment group and with better feeding practices and growth outcomes, providing preliminary evidence that early intervention promoting more responsive feeding profiles may improve infant outcomes.